First Experience With the ICD 16.5 Mini-Scleral Lens for Optic and Therapeutic Purposes. Issue 1 (January 2018) - Suarez, Cyrielle; Madariaga, Virginie; Lepage, Benoît; Malecaze, Marie; Fournié, Pierre; Soler, Vincent; Galiacy, Stéphane; Mély, René; Cassagne, Myriam; Malecaze, François
Abstract : Objectives: To evaluate the success rate, efficacy, and safety of the ICD 16.5 mini-scleral gas permeable (GP) contact lens. Methods: This prospective study included referred consecutive patients with irregular corneas and severe ocular surface disease (OSD) in treatment failure. All patients were fitted with the ICD 16.5 mini-scleral GP lens. Even though we had some limited experience with scleral lenses, it was our first experience with the ICD 16.5 mini-scleral GP lens. Efficacy was assessed by comparing best-corrected visual acuity (BCVA) with the mini-scleral lens to baseline BCVA. A subjective visual functioning questionnaire (comfort score, visual quality score, handling rating, and wearing time) was administered in a face-to-face structured interview. Results: Thirty-nine eyes of 23 patients with a mean age of 43±16 years were included. Fitting indications were keratoconus (46%), post-penetrating keratoplasty (21%), other irregular astigmatism (15%), and severe OSD (18%). Twenty-five eyes (64%) were successfully fitted with an 18-month follow-up. The mini-scleral GP lens BCVA was 0.16 logarithm of the minimum angle of resolution (logMAR; 20/25) versus a baseline BCVA of 0.44 logMAR (20/63; P <0.001). Comfort and visual quality scores were 8.5/10 and 7.5/10, respectively. No complications were detected in 96% of the eyes (95% confidence interval, 76.1%–99.4%). One eye experienced corneal graft swelling. Conclusions: The present findings suggest that the ICD 16.5 mini-scleral GP lens is an effective and safe alternative for managing challenging corneas in a therapeutic impasse.